The role of motivation in the process of formation of future paramedics’ maturity to perform professional activity - Chornobryva, N. V. (Problems of Engineer-Pedagogical Education, 2018)
The article deals with the concept of motivation and the stages of its formation which are as follows: the emergence of needs; strategy development and identification of the ways to meet requirements; definition of activity tactics and phased implementation of the actions; satisfaction of needs and reception of material or spiritual rewards. The paper considers the following groups of motives, which are necessary for the future specialist’s maturity formation, namely social, cognitive, professional, and self-interest motives, and presents their characteristics. The viewpoint of scientists on the interpretation of the concept of "professional motivation" has been elucidated. The stages of improving future paramedics’ motivation for professional activity have been determined and they are as follows: increase of personal motivation for the professional advancement in their professional activity; creation of a success mindset regarding professional activity; intensification of the increase of the interest in professional activity; formation of high motivation for personal and professional self-development. The stages have been introduced by means of creating a positive orientation towards professional practical activity (training "I am a Future Specialist"), creating situations for theoretical maturity self-analysis and evaluation of personal practical maturity (training "I am Moving Towards Professional Excellence"), creating situations of success on the basis of professional achievements, both in educational and practical activities (training simulation game "A Step to Success"); creating a success mindset regarding professional activity (training game – transaction "Your Professional Choice"); encouraging s positive interest in professional training and a high motivation for personal development by consolidating the situations of success during the work experience internship and the positive result in reference to the level of professional competence growth (the method "The Motives of Mastering the Profession" (in A. Rean’s modification)).